WORD-FORMING ASPECT OF COMPUTER SLANG IN INTERNET DISCOURSE - Mukimova Gulandom Akhatovna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Summary: In this article is considered sources and ways of formation of slang words in the language environment of the Internet